Crude protein in low‐fish meal diets for juvenile Litopenaeus vannamei can be reduced through a well‐balanced supplementation of essential amino acids. Issue 6 (28th March 2019) - Nunes, Alberto J. P.; Sabry‐Neto, Hassan; Masagounder, Karthik
Abstract : The use of supplemental essential amino acids (EAAs) has been shown to provide an opportunity to minimize excess levels of crude protein (CP) in animal feeds. The present study investigated the effect of reducing the amount of CP in low‐fish meal diets (5%) for juvenile Litopenaeus vannamei . Four sets of diets were prepared containing (% on a fed basis, mean ± SD ) 31.24 ± 0.71, 33.70 ± 0.41, 36.90 ± 0.44, and 39.63 ± 0.14% CP, with each protein level containing a total dietary methionine (Met) (Met + Cys) level of 0.56 ± 0.02 (1.07 ± 0.23), 0.71 ± 0.01 (1.22 ± 0.20), 0.88 ± 0.02 (1.38 ± 0.22), or 1.04 ± 0.02% (1.55 ± 0.18%). Shrimp of 1.00 ± 0.08 g were stocked in 84 outdoor tanks of 1 m 3 at a rate of 100 shrimp/m 2 and raised for 75 days. Final survival ranged from 83 to 97% and was unaffected by Met content. Both survival and yield were significantly depressed when shrimp were fed the 31% CP diet. Shrimp grew at a weekly rate of between 0.79 and 0.97 g, achieving a final body weight (BW) in excess of 10.8 g. There was a significant interaction between CP and Met over BW. Shrimp fed 0.56% Met achieved the lowest BW at harvest. Increasing CP beyond 34% did not enhance BW. With a dietary Met content of 0.71%, the highest BW was achieved with 34% CP compared to other levels. There was a significant improvement in Feed Conversion Ratio (FCR) when CP was raised from 31 to 34%. Similarly, dietary Met levels above 0.71% resulted in a significantly better FCR compared to 0.56%. Our study has shown that, if dietary Met (Met + Cys) meets a minimum of 0.71% (1.22%), levels of CP could be reduced from 40 to 34% without adverse effects on shrimp performance.